Empirical Analysis Of Productivity And Resource-Use-Efficiency In Ghana’s Cocoa Industry: Evidence From Bibiani-Anhiawso-Bekwai District. - Gideon, Danso-Abbeam (2011)
A Thesis Submitted To The School Of Graduate Studies, Kwame Nkrumah University Of Science And Technology, Kumasi, In Partial Fulfilment Of The Requirements For The Award Of Master Of Philosophy Degree In Agricultural Economics.